Dynamics of the restoration of physical trails in the grass-cutting ant Atta capiguara (Hymenoptera, Formicidae) - Caldato, Nadia [UNESP] (2016)
Dynamics of the restoration of physical trails in the grass-cutting ant Atta capiguara. Leaf-cutting ants of the genus Atta build long physical trails by cutting the vegetation growing on the soil surface and removing the small objects they find across their path. Little is known on the dynamics of trail construction in these ants. How much time do they need to build a trail? To answer this question we selected six trails belonging to two different nests of A. capiguara and removed on each trail a block of soil of 20 cm × 15 cm that included a portion of the physical trail. This block was then replaced by a new block of the same size that was removed in the pasture near the trail and that was uniformly covered by the same type of vegetation as that found on the block of soil that was removed. The time required to restore the trail was then evaluated by the length of the grass blades found along the former location of the trail. The results show that ants rapidly restore the portion of the physical trail that was interrupted, which suggests that they could also do the same after their trails have been recolonized by the vegetation.